2010
DOI: 10.1186/1476-4598-9-122
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Transforming Growth Factor-β pathway inhibits human basal-like breast cancer metastasis

Abstract: BackgroundTransforming Growth Factor β (TGF-β) plays an important role in tumor invasion and metastasis. We set out to investigate the possible clinical utility of TGF-β antagonists in a human metastatic basal-like breast cancer model. We examined the effects of two types of the TGF-β pathway antagonists (1D11, a mouse monoclonal pan-TGF-β neutralizing antibody and LY2109761, a chemical inhibitor of TGF-β type I and II receptor kinases) on sublines of basal cell-like MDA-MB-231 human breast carcinoma cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 56 publications
6
117
0
1
Order By: Relevance
“…39 MDA-MB-231 cells belong to those tumor cells, which are resistant to the growth inhibition of TGF-b1, although they are responsive with respect to TGF-b1-induced gene expression. 40 This supports the role of autocrine TGF-b1 in tumor progression in this cell type. SPP1 is a TGF-b1 target gene.…”
Section: Discussionsupporting
confidence: 73%
“…39 MDA-MB-231 cells belong to those tumor cells, which are resistant to the growth inhibition of TGF-b1, although they are responsive with respect to TGF-b1-induced gene expression. 40 This supports the role of autocrine TGF-b1 in tumor progression in this cell type. SPP1 is a TGF-b1 target gene.…”
Section: Discussionsupporting
confidence: 73%
“…TAMs contribute to tumor growth and metastasis by secreting MMPs that promote extracellular matrix remodeling; angiogenic factors that increase blood vessel formation; and cytokines, chemokines, and growth factors that enhance tumor growth [18,19]. Specifically, TAMs have been reported to produce VEGF, epidermal growth factor, basic fibroblast growth factor, platelet-derived growth factor, IL-6, MCP-1, CXCL18, CXCL12, and YKL-40/CHI3L1 [16,[20][21][22][23][24][25]. YKL-40/CHI3L1 induces the expression of MCP-1/CCL2 and IL-8/CXCL2, which are chemoattractants for monocytes/ macrophages and neutrophils [16].…”
Section: Tumor-associated Inflammationmentioning
confidence: 99%
“…TGF-␤'s disease promoting activities, together with animal studies that have demonstrated beneficial effects of inhibiting TGF-␤ in models of cancer and fibrosis (15)(16)(17)(18)(19)(20)(21)(22), have made them important targets for the development of inhibitors. However, despite clinical trials ongoing for nearly 2 decades using receptor kinase inhibitors, neutralizing antibodies, and other approaches, no TGF-␤ inhibitors have been approved for clinical use in humans (23,24).…”
mentioning
confidence: 99%